Question
upstudy study bank question image url

(b) Find the slope of the following curves at the given points. (i) \( y^{2}+x^{2}=y^{4}-2 x \) at \( (-2,1) \) and \( (-2,-1) \)

Ask by Flynn Brooks. in Pakistan
Nov 24,2024

Upstudy AI Solution

Tutor-Verified Answer

Answer

The slope at \((-2, 1)\) is \(-1\) and at \((-2, -1)\) is \(1\).

Solution

To find the slope of the curve defined by the equation \( y^2 + x^2 = y^4 - 2x \) at the given points, we will use implicit differentiation. 1. **Differentiate both sides of the equation with respect to \( x \)**: The equation is: \[ y^2 + x^2 = y^4 - 2x \] Differentiating both sides: - The left side: \[ \frac{d}{dx}(y^2) + \frac{d}{dx}(x^2) = 2y \frac{dy}{dx} + 2x \] - The right side: \[ \frac{d}{dx}(y^4) - \frac{d}{dx}(2x) = 4y^3 \frac{dy}{dx} - 2 \] Setting the derivatives equal gives: \[ 2y \frac{dy}{dx} + 2x = 4y^3 \frac{dy}{dx} - 2 \] 2. **Rearranging the equation**: \[ 2y \frac{dy}{dx} - 4y^3 \frac{dy}{dx} = -2 - 2x \] \[ (2y - 4y^3) \frac{dy}{dx} = -2 - 2x \] \[ \frac{dy}{dx} = \frac{-2 - 2x}{2y - 4y^3} \] \[ \frac{dy}{dx} = \frac{-1 - x}{y - 2y^3} \] 3. **Evaluate the derivative at the points \((-2, 1)\) and \((-2, -1)\)**: - **At the point \((-2, 1)\)**: \[ \frac{dy}{dx} = \frac{-1 - (-2)}{1 - 2(1)^3} = \frac{-1 + 2}{1 - 2} = \frac{1}{-1} = -1 \] - **At the point \((-2, -1)\)**: \[ \frac{dy}{dx} = \frac{-1 - (-2)}{-1 - 2(-1)^3} = \frac{-1 + 2}{-1 + 2} = \frac{1}{1} = 1 \] 4. **Final results**: - The slope of the curve at the point \((-2, 1)\) is \(-1\). - The slope of the curve at the point \((-2, -1)\) is \(1\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the slope of the curve defined by the equation \( y^{2} + x^{2} = y^{4} - 2x \) at the points \( (-2,1) \) and \( (-2,-1) \), you'll need to use implicit differentiation. First, differentiate both sides of the equation with respect to \( x \): 1. The derivative of \( y^{2} \) is \( 2y \frac{dy}{dx} \). 2. The derivative of \( x^{2} \) is \( 2x \). 3. The derivative of \( y^{4} \) is \( 4y^{3} \frac{dy}{dx} \). 4. The derivative of \( -2x \) is \( -2 \). This gives us the equation: \[ 2y \frac{dy}{dx} + 2x = 4y^{3} \frac{dy}{dx} - 2 \] Rearranging this equation to isolate \( \frac{dy}{dx} \) yields: \[ (2y - 4y^{3}) \frac{dy}{dx} = -2x + 2 \] \[ \frac{dy}{dx} = \frac{-2x + 2}{2y - 4y^{3}} \] Now plug in the points: At \( (-2, 1) \): \[ \frac{dy}{dx} = \frac{-2(-2) + 2}{2(1) - 4(1)^{3}} = \frac{4 + 2}{2 - 4} = \frac{6}{-2} = -3 \] At \( (-2, -1) \): \[ \frac{dy}{dx} = \frac{-2(-2) + 2}{2(-1) - 4(-1)^{3}} = \frac{4 + 2}{-2 + 4} = \frac{6}{2} = 3 \] So, the slopes at the points \( (-2, 1) \) and \( (-2, -1) \) are \( -3 \) and \( 3 \), respectively.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy